Insights on Interactive Tabletops: A Survey of Researchers and Developers - Benko, Hrvoje; Morris, Meredith Ringel; Brush, A.J.; Wilson, Andy (Microsoft, 2009)
Recently, interest in tabletop computing has surged, both within the research community and within the commercial sector. However, given the early stage of interactive tabletop adoption and current low availability, it is difficult to find end users with extended experience in using such devices. We conducted a survey of 58 tabletop researchers and developers, the only available population with longer-term tabletop use experience, to find out how they use their devices, what they use them for, and what features they consider important for novice, single-user, and collaborative scenarios. While not without inherent biases, their answers suggest important directions for further research in designing and evaluating interactive tabletop systems, including identification of obstacles to mainstream adoption, and input and ergonomic challenges.